PEMANFAATAN SERBUK CANGKANG LOKAN SEBAGAI BAHAN PENGGANTI PASIR DALAM PEMBUATAN PAVING BLOCK - Mulyati Mulyati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study uses lokan shellpowder as an alternative material for sand in the manufacture of paving block. The purpose of this study was to determine the compressive strength of paving block resulting from the use of lokan shell powder as a substitute for sand. The paving block specimens used rectangular molds measuring 20 cm x 10 cm x 6 cm, with a ratio of cement and sand mixture of 1:3 at 28 days of testing, with conventional/manual manufacturing methods. Variation in the use of lokan shell powder as a substitute for sand are 0%, 10%, 20%, and 30%. The results of the compressive strength test of paving block were obtained, for the use of 0% lokan shell powder was 8.67 MPa, the use of 10% lokan shell powder was 8.88 MPa, the use of 20% lokan shell powder was 10.2 MPa, and thw use of 30% lokan shell powder was 9.06 MPa. Thus it can be stated that lokan shell powder can be used as a substitute for sand up to 30% in the manufacture of paving blocks.